Preparation of an Information Technology Master Plan Using the TOGAF Enterprise Architecture Framework Case Study of PT Wijaya Karya (Persero) Tbk. 2018 Year - Aziz Ma'sum; Ernawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Long-term planning in the development of information systems is useful to support the company's vision and mission called Information Technology (IT) Master Plan. The IT Master Plan explains things related to the company's vision and mission to the information technology project management planning and basically the IT Master Plan is the conversion of the company's strategy into an information system technology implementation plan. The first step in building an information technology infrastructure is to make an IT Master Plan first. The IT Master Plan is made referring to the company's business strategy through understanding the organization's business architecture and technology trends. The decision makers will formulate strategic matters related to the implementation of IT infrastructure. TOGAF is one of the frameworks that is often used in preparing this IT Master Plan. The TOGAF framework consists of methods and components for assessing, creating, deploying and maintaining enterprise architectures. With a broad scope, complete, easy to understand and utilizing the terminology concept of ISO/IEC 42010: 2007 makes TOGAF as an option. TOGAF is developed by The Open Group and is free/open source. The IT Master Plan must always be updated in accordance with the company's business developments. Changes and company dynamics related to information technology and systems must be contained in the IT Master Plan.